The networked nonprofit connecting with social media to drive change - Kanter, Beth, 1957-; Fine, Allison H., 1964- (San Francisco : Jossey-Bass, 2010)
"This groundbreaking resource offers a set of guiding principles to help nonprofit leaders navigate the transition from top-down organizations to a networked approach enabled by technology. The book contains specific strategies for implementation and secrets to success from nonprofits who have used new social media tools effectively themselves. It also offers effective exercises and how-to's for implementation. A key element of this book is interviews with current nonprofit managers who have learned how to jump into the social media fray without a net and thrived because of it"--
Introducing networked nonprofits -- Nonprofit challenges and trends -- Understanding social networks -- Creating a social culture -- Listening, engaging, and building relationships -- Building trust through transparency -- Making nonprofit organizations simpler -- Working with crowds -- Learning loops -- From friending to funding -- Governing through networks.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nonprofit organizations; Social networks; Electronic books